Invectiva e identidad en los discursos de oratoria de Cicerón: análisis del locus de la ‘infirmitas ingeni’ - Cairo, María Emilia (2023)
The aim of this paper is to examine in Cicero’s oratory speeches the criticisms of his opponents regarding either their lack of erudition or their poor intellectual abilities. From our viewpoint, this original locus of invective is closely linked to the consolidation of a new intellectual nobilitas at the end of the Roman Republic and is especially relevant in the context of Cicero’s return from exile.